Teachers' Questioning Strategies During English Class Interaction in Junior Secondary School - Ananda, Ismawati; Noni, Nurdin; Korompot, Chairil Anwar (State University of Makassar, 2022)
The objective of this study was to find out the teacher’s questioning strategy in teaching English at SMP Muhammadiyah Limbung and to find out the improvement of students’ motivation in learning English through the teacher’s questioning strategy. This research used the qualitative method. This study consisted of 10 subjects: 2 teachers and 8 students. Data were collected through observation and interviews. The results of the data analysis show that teachers use questioning strategies by applying two types of questioning strategies and using two types of questions in each teaching meeting. The use of probing question strategy which belongs to the display question type, and divergent question strategy which belongs to the referential question type, in asking questions is dominant. This depends on the material the teacher is presenting to the students. The findings of this study also show a positive impact on students’ learning motivation on the use of questioning strategies teachers apply in English learning activities in the classroom.Keywords: English Teacher Questions, Questions Strategies, and Students’ Motivation